Integrative Model of School Facilities and Infrastructure Management in Improving the Quality of Learning in Simeulue Regency - Adriansah, Adriansah; Usman, Nasir; AR, Murniati; Nonisafriani, Nonisafriani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study aims to analyze and develop an integrative management model of school facilities and infrastructure in an effort to improve the quality of learning in the State Junior High School (SMPN) Simeulue Regency. The focus of the research is directed at the synergy of the planning, organizing, implementing, and supervision (POAC) functions to create an efficient, accountable, and sustainable school management system. Methods: This study used a descriptive qualitative approach with a multisite design. Data were collected through interviews, observations, and documentation at the four State Junior High Schools. Data validation is carried out using triangulation techniques of sources and methods, while data analysis is conducted through the stages of data reduction, data presentation, and conclusion drawn. Results: The results of the study show that the implementation of integrative management of facilities and infrastructure has been carried out systematically and collaboratively so that it has a positive impact on student learning comfort, teacher professionalism, and learning effectiveness. The process includes participatory planning, transparent procurement, and ongoing maintenance, according to POAC principles. Novelty: This research produces a new model of integrative management of school facilities and infrastructure that combines the theory of the education system and the principle of Total Quality Management (TQM), emphasizing collaboration, accountability, and local adaptability as the main factors for improving the quality of learning in the context of education in the archipelago.​